Synthesis and Pharmacological Evaluation of a series of the Agomelatine Analogues as Melatonin MT1/MT2 Agonist and 5‐HT2C Antagonist. Issue 11 (12th September 2013) - Ettaoussi, Mohamed; Sabaouni, Ahmed; Pérès, Basile; Landagaray, Elodie; Nosjean, Olivier; Boutin, Jean A.; Caignard, Daniel‐Henri; Delagrange, Philippe; Berthelot, Pascal; Yous, Saïd
Abstract Agomelatine is a naphthalenic analogue of melatonin that is in clinical use for the treatment of major depressive disorders. Interestingly, while agomelatine exhibits potent affinity for melatonin receptors, it binds with only moderate affinity to the serotonin 5‐HT2C receptor. Optimization of agomelatine toward this target could further potentiate its clinical efficacy. To explore this hypothesis and to access derivatives in which a key point of agomelatine metabolism is blocked, a series of naphthalenic derivatives was designed and synthesized as novel analogues of agomelatine. Most of the prepared compounds exhibited good binding affinity at the melatonin MT1 and MT2 receptor subtypes. Two compounds, an acetamide and an acrylamide derivative, exhibited good binding affinities at both the human melatonin (MT) receptors and the serotonin 5‐HT2C receptor subtype, with pKi values of 7.96 and 7.95 against MT1, 7.86 and 8.68 against MT2, and 6.64 and 6.44 against 5‐HT2C, respectively.